Exploration of reference models in a public university system. Issue 1 (16th January 2019) - Alexander, Stephanie; Wakimoto, Diana K.
Abstract : Purpose: This study aims to investigate the reference and public service models used at academic libraries in the California State University system. Design/methodology/approach: This exploratory study used a qualitative mixed methods design with an online survey and follow-up interviews with public services librarians. Findings: The majority of the libraries in this study continue to use a traditional reference model with a physical desk staffed by librarians. Some libraries have moved to tiered or on-call reference using students and staff to triage patron questions. The majority of libraries' public service points also follow a traditional configuration with separate service points for reference and other library public services. Research limitations/implications: As this research is limited to one public university system, the results may not be generalizable to all academic libraries. Replicating this research in other systems would increase the generalizability of the results and allow for the generation of potential best practices for reference models and public service point configurations. Practical implications: Librarians who are considering changes to their reference models and service point layouts can use the results as a starting point for conversations about the benefits and challenges of various models as well provide support to create an environment where changes to the models can be successfully implemented. Originality/value: This study is one of the few to investigate multiple academic libraries' approaches to reference and public services in the research literature. As such, it addresses a gap in the literature that case studies alone cannot fill.